The voltammetric determination of peroxynitrite at a mercury film electrode; New Journal of Chemistry; Vol. 31, iss. 3 - Zakharova E. A. Elsa Arminana; Yurmazova T. A. Tatyana Aleksandrovna; Nazaarov B. F.; Wildgoose G. G.; Compton R. G. (2007, 2007)
Title screen